PENGARUH DIMENSI VISUAL MERCHANDISING TERHADAP IMPULSE BUYING PADA SUZUYA MALL KOTA BANDA ACEH - Faras Muwahhid Fauzi; Fakhrurrazi Amir (Departemen Manajemen, 2019)
Abstract: This study aims to examine the influence of Visual Merchandising dimensions consisting of Window Display, Mannequin Display, Floor Merchandising, and Promotional Signage on consumer Impulse Buying behavior of Suzuya Mall Banda Aceh. The sampling method in this study uses accidential sampling technique where respondents are people who meet directly with researchers in the location. The sample of 200 respondents and the data analysis method used is multiple regression analysis. The results showed that partially Window Display, Mannequin Display, Floor Merchandising, and Promotional Signage had a significant effect on Impulse Buying. Simultaneous testing shows Window Display, Mannequin Display, Floor Merchandising, and Promotional Signage have a significant effect on Impulse Buying behavior on consumers of Suzuya Mall Banda Aceh.Keywords: Window Display, Mannequin Display, Floor Merchandising and Promotional Signage.